2005
DOI: 10.1016/j.immuni.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Nef-Mediated Lipid Raft Exclusion of UbcH7 Inhibits Cbl Activity in T Cells to Positively Regulate Signaling

Abstract: Lentiviral Nef increases T cell signaling activity, but the molecular nature of the stimulus involved is incompletely described. We explored CD4 T cell lipid raft composition in the presence and absence of Nef. Here, the E2 ubiquitin-conjugating enzyme UbcH7, which acts in conjunction with c-Cbl, is absent from lipid rafts. This Nef-mediated exclusion is associated with failure of ubiquitination of activated Vav. In the presence of Nef, lipid raft Cdc42 is activated and forms a ternary complex between the c-Cb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 55 publications
(59 reference statements)
2
30
0
2
Order By: Relevance
“…Such effects are generally consistent with previous reports on the disassembly of F-actin structures by Nef in fibroblasts (14,33). Interestingly, Nef is known to activate Rac1 and Cdc42 in T-lymphocytes (15,44) but, as shown herein, disrupts cytoskeletal structures induced by these GTPases. This might reflect that both, seemingly opposing, activities of Nef are independently exerted by distinct Nef subpopulations in cells.…”
Section: Discussionsupporting
confidence: 93%
“…Such effects are generally consistent with previous reports on the disassembly of F-actin structures by Nef in fibroblasts (14,33). Interestingly, Nef is known to activate Rac1 and Cdc42 in T-lymphocytes (15,44) but, as shown herein, disrupts cytoskeletal structures induced by these GTPases. This might reflect that both, seemingly opposing, activities of Nef are independently exerted by distinct Nef subpopulations in cells.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, other mem- brane-associated HIV-1 proteins, including Env, Nef, Vpu, and Tat, may interact with membrane microdomains. In particular, Nef has been proposed to alter lipid rafts and their constituent lipids and proteins (2,99,127,143,144). To control for the effects of other HIV-1 proteins on microdomains, we compared the copatching of microdomain markers in cells transfected with a WT HIV-1 molecular clone or cells transfected with a molecular clone containing multiple MA mutations (1GA/6A2T).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Nef affects the basal states of T-cell activation and the responsiveness of T lymphocytes to TCR signaling. [19][20][21][22] Initial studies with overexpression strategies in cell lines reached contradicting conclusions about the effects of Nef on TCR signaling. More recent work with viral infection and/or primary target T cells revealed that Nef moderately enhances distal responses to exogenous TCR stimulation by mitogens or anti-TCR Abs.…”
mentioning
confidence: 99%